Assessing the Potentials of a Plant-Based Coagulant (Cyperus Esculentus Pulp) as alternative to Alum in Conventional Water Treatment Process - Akuboh, D. O.; Saidu, M.; Abdulkareem, A. S.; Busari, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Globally, chemical coagulants such as alum are employed in water treatment during coagulation and flocculation process to improve drinking water quality. This process has an effect on human health. This research was carried out to assess the potentials of a plant-based coagulant (Cyperus esculentus Pulp) as substitute for alum or as coagulation aids. The water sample from river Gorao along Minna-Bida Road in Niger State were obtained in line with the standard laboratory procedures of the American Public Health Association (APHA) for the evaluation of the efficacy of the two coagulants (Plant-based Coagulant – Cyperus esculentus) and Aluminium Sulphate (Alum). Jar Test was done for some turbidity range. The results showed Turbidity and Colour removal efficiencies of 80.47% and 55.37% respectively. The Water Quality Index (WQI) shows that Cyperus esculentus produces good quality water (grade B) with WQI of 44.5. Recommendations arising from this study includes that further investigation should be carried out on other potential plant-based coagulants. Yellow variety of Cyperus esculentus should be investigated for its coagulation potentials and the use of Cyperus esculentus as coagulant is recommended as coagulant aid for reduction of turbidity in water.